Production Unit of Vocational High School: Learning Resource and Enterpreneurships Place - Sumual, Herry; Sumual, Hendro M. (INVOTEC, 2016)
The purpose of this research is to develop an implementation model of production unit at Vocational High School that functions as learning resource and business place. The research method used is Research and Development. Sample units are 2 vocational high schools (public school) and 2 vocational high schools (private school). The results of the research are: The model of production unit at Vocational High School (VHS). This model has been tested limitedly with experts and party from Vocational High School and Department of Education and Culture of Manado City. Through this production model resulted, it can be suggested to party of school to manage the production unit that exists in each school very well as a form of services as well as to produce the goods